Quantitative Trait Loci Mapping and Association Analysis of Solanesol Content in Tobacco (Nicotiana tabacum L.) - Liu, Jing; Xiang, Dehu; Du, Yongmei; Zhang, Zhongfeng; Zhang, Hongbo; Cheng, Lirui; Fu, Qiujuan; Yan, Ning; Ju, Fuzhu; Qi, Chaofan; Lei, Yunkang; Wang, Jun; et al. (Agronomy (Basel), 2024)
Solanesol, which accumulates predominantly in the leaves of tobacco plants, has medically important bioactive properties. To investigate the genetic basis of solanesol in tobacco (Nicotiana tabacum), the solanesol contents of 222 accessions, 206 individuals from an N. tabacum Maryland609 (low-solanesol) × K326 (high-solanesol) F2 population and their corresponding F1 self-pollinations, were determined using ultra-performance liquid chromatography. Genome-wide quantitative trait locus (QTL) and association analysis were performed to identify QTLs and markers associated with solanesol content based on simple sequence repeat molecular markers. A total of 12 QTLs underlying solanesol content were mapped to seven linkage groups (LGs), with three of the QTLs (QTL3-1, QTL21-6, and QTL23-3) explaining 5.19–10.05% of the phenotypic variation. Association analysis revealed 38 significant marker-trait associations in at least one environment. The associations confirmed the QTLs located on LG3, LG10, LG14, LG21, and LG23, while new elite makers were located on 11 additional LGs, each explaining, respectively, 5.16–20.07% of the phenotypic variation. The markers LG14-PT54448, LG10-PT60114-2, LG10-PT60510, LG10-PT61061, and LG-21PT20388 may be useful for molecular-assisted selection of solanesol content in tobacco leaves. These results increase our understanding of the inheritance of solanesol-associated genes and will contribute to molecular-assisted breeding and further isolation of regulatory genes involved in solanesol biosynthesis in tobacco leaves.